2017
DOI: 10.15171/jcvtr.2017.03
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a therapeutic lifestyle change diet and supplementation with Q10 plus L-carnitine on quality of life in patients with myocardial infarction: A randomized clinical trial

Abstract: Introduction: Myocardial infarction (MI) has a deleterious effect on quality of life (QoL), which can affect cardiac prognosis after MI. Thus, new strategies have to be identified for improving the QoL. To our knowledge, no studies have been conducted on the impact of therapeutic lifestyle change (TLC) diet and L-carnitine plus Q10 supplementation on QoL after MI. Methods: The study aimed to measure 128 MI patients’ QoL using MacNew QoL questionnaire (global scales and physical, emotional, and social subscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
16
0
4
Order By: Relevance
“…It has been estimated that men with metabolic syndrome have 2–3 times greater probability for cardiovascular disease (CVD) than those without metabolic syndrome [ 2 – 4 ]. Overall, metabolic syndrome is associated with a twofold increase in the risk of CVD, CVD mortality, and stroke, and a 1.5-fold increase in risk of all-cause mortality [ 5 7 ]. In fact, coronary artery disease (CAD) is among the main causes of death in developed countries, while it has a growing epidemic in developing countries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that men with metabolic syndrome have 2–3 times greater probability for cardiovascular disease (CVD) than those without metabolic syndrome [ 2 – 4 ]. Overall, metabolic syndrome is associated with a twofold increase in the risk of CVD, CVD mortality, and stroke, and a 1.5-fold increase in risk of all-cause mortality [ 5 7 ]. In fact, coronary artery disease (CAD) is among the main causes of death in developed countries, while it has a growing epidemic in developing countries [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 In another study, Sharifi et al showed that both a therapeutic lifestyle-change diet and supplementation with CoQ 10 (150 mg/day) and L-carnitine had a positive effect on the physical and emotional subscales of the MacNew questionnaire in patients with myocardial infarction. 17 In addition, Morris et al illustrated the CoQ 10 's potential role in improving QOL in patients with Parkinson's disease and fibromyalgia. Also, it showed antidepressive effects and significantly reduced fatigue and improved ergonomic performance during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies on the effectiveness of CoQ 10 on QOL in different diseases have indicated that this supplement can have a beneficial effect on QOL. [16][17][18] However, there have been few studies on breast cancer, 9 and to our knowledge, a trial evaluating the effect of CoQ 10 alone in breast cancer patients has not been done yet. Considering the high prevalence of breast cancer, in addition to its importance and effects on all life dimensions of patients, focusing on QOL as it relates to health and finding solutions to ameliorate QOL of these patients seems necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural changes following an MI are critical for addressing the risk of future morbidity and mortality (Gaalema, Elliott, Morford, Higgins, & Ades, ). Adherence to secondary prevention guidelines that include the modification of lifestyle behaviours such as quitting smoking, improving diet and increasing moderate physical activity can significantly reduce the risk of recurrent events or deaths after MI (Sharifi, Eftekhari, Ostovan, & Rezaianazadeh, ; Wallert, Madison, Held, & Olsson, ).…”
Section: Introductionmentioning
confidence: 99%